Word formation of slang used in selected songs of SZA’s sos album - Syahidah, Nuha Nur (Yayasan Mitra Persada Nusantara, 2024)
This research concerns word formation processes of slang in selected songs of SZA’s SOS Album which are “SOS,” “Snooze,” and “Low.” This research aims to: 1) analyze the types of word formation of slang words based on Yule's theory utilized in selected songs 2) analyze their meaning, and 3) analyze which songs, word-formation processes, and slang words dominate and are used most frequently. This research uses a descriptive qualitative method. This research also uses observation as a method of data collection and distributional methods to analyze the data. The theory uses in this research is Yule’s theory (2006) of the word formation process. This research concludes that there are 149 times Slang words that appear in selected songs of SZA's album SOS, with